Peran Pelatih di Sekolah Luar Biasa Aisyiyah Sijunjung Terhadap Prestasi Renang Siswa Disabilitas Intelektual - Ath-Thahiratul Annesa; Zulmiyetri Zulmiyetri; Elsa Efrina; Safaruddin Safaruddin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the role of coaches at SLB Aisyiyah Sijunjung in improving the swimming achievements of students with intellectual disabilities. The study used a qualitative approach with a case study design. The main informants were swimming coaches, while additional informants were sports teachers involved in the training process. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that coaches played an important role in improving students’ swimming achievements through psychological, physical, social, and character-building approaches. Coaches applied adaptive strategies such as simple communication, direct demonstrations, gradual and repetitive training, as well as continuous motivation and positive reinforcement adjusted to students’ characteristics. The obstacles faced included limited concentration, unstable emotions, differences in motor abilities, and limited training facilities. However, these obstacles were overcome through individual approaches, collaboration with teachers and parents, and consistent training programs. The study implies that adaptive coaching and supportive training environments greatly influence students’ confidence, discipline, social interaction, and achievements in regional, national, and international swimming competitions